Respuesta :
Distribute the negative to the terms in parentheses.
-2x + 3= 5 -9x-2
Combine like terms
-2x + 3= -9x+3
Add 9x to both sides
7x + 3= 3
Subtract 3 from both sides
7x= 0
Divide 7 on both sides
X=0
-2x + 3= 5 -9x-2
Combine like terms
-2x + 3= -9x+3
Add 9x to both sides
7x + 3= 3
Subtract 3 from both sides
7x= 0
Divide 7 on both sides
X=0
To solve this equation you have to :
First, develop 5 - (9x + 2) :
.
-2x + 3= 5 - 9x-2
Afterwards you combine :
-2x + 3= -9x+3
To removed -9x in the right member, add 9x to both sides. That gives :
7x + 3= 3
Subtract 3 from both sides
7x= 0
Finally, instead of getting 7x in left member, we want to have merely "x". So you have to divide 7 on both sides.
X=0.
Hope this helps !
Photon
First, develop 5 - (9x + 2) :
.
-2x + 3= 5 - 9x-2
Afterwards you combine :
-2x + 3= -9x+3
To removed -9x in the right member, add 9x to both sides. That gives :
7x + 3= 3
Subtract 3 from both sides
7x= 0
Finally, instead of getting 7x in left member, we want to have merely "x". So you have to divide 7 on both sides.
X=0.
Hope this helps !
Photon